A biochemical study of the distribution of collagen and its crosslinks in knee ligaments and the patellar tendon. (October 2014) - Hanada, Mitsuru; Takahashi, Masaaki; Suzuki, Daisuke; Abe, Masashi; Matsuyama, Yukihiro
Abstract Purpose: The purpose of this study was to investigate biochemical differences in collagen crosslinks from different locations within the ligaments and a tendon of the human knee. Materials and Methods: The anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), medial collateral ligament (MCL), lateral collateral ligament (LCL), and patellar tendon (PT) were obtained from 24 cadavers (13 men and 11 women) whose average age at the time of death was 84.8 years. Ligaments and PT samples were obtained from the femoral and tibial insertions and the midsubstance. Hydroxyproline (Hyp) and collagen crosslinks, including pyridinoline (Pyr) and pentosidine (Pen), were compared among the different sites. Results: The midsubstance Hyp concentration was greater than at the femoral and tibial insertions in the ACL (p = 0.00124 and 0.000255, respectively) and PCL (p = 0.00036 and 0.042, respectively). The Pyr:collagen ratio did not differ among sites in any of the ligaments or PT. The Pen:collagen ratio at the midsubstance was greater than at the femoral and tibial insertions in the ACL (p = 0.00022 and 0.00025, respectively) and LCL (p = 0.000081 and 0.000021, respectively) and was greater at the femoral insertion in the MCL (p = 0.00010). Conclusions: The mature collagen crosslink Pyr was not different in distribution in knee ligaments and the PT. Pen increased at the midsubstance ligaments and the PT. As increased Pen may represent ligament degeneration, this may indicate that degeneration may progress more rapidly at the midsubstance than at the insertion sites of a ligament.